Autophagy Inhibitor Chloroquine Enhanced the Cell Death Inducing Effect of the Flavonoid Luteolin in Metastatic Squamous Cell Carcinoma Cells - Verschooten, Lien; Barrette, Kathleen; Van Kelst, Sofie; Rubio Romero, Noemí; Proby, Charlotte; De Vos, Rita; Agostinis, Patrizia; Garmyn, Marjan (PLOS ONE, 2012)
Background Flavonoids are widely proposed as very interesting compounds with possible chemopreventive and therapeutic capacities. Methods & Results In this study, we showed that in vitro treatment with the flavonoid Luteolin induced caspase-dependent cell death in a model of human cutaneous squamous cell carcinoma (SCC) derived cells, representing a matched pair of primary tumor and its metastasis. Notably, no cytotoxic effects were observed in normal human keratinocytes when treated with similar doses of Luteolin. Luteolin-induced apoptosis was accompanied by inhibition of AKT signaling, and sensitivity decreased with tumor progression, as the primary MET1 SCC cells were considerably more sensitive to Luteolin than the isogenic metastatic MET4 cells. Extensive intracellular vacuolization was observed in Luteolin-treated MET4 cells, which were characterized as acidic lysosomal vacuoles, suggesting the involvement of autophagy. Transmission electron microscopy, mRFP-GFP-LC3 assay and p62 protein degradation, confirmed that Luteolin stimulated the autophagic process in the metastatic MET4 cells. Blocking autophagy using chloroquine magnified Luteolin-induced apoptosis in the metastatic SCC cells. Conclusion Together, these results suggest that Luteolin has the capacity to induce selectively apoptotic cell death both in primary cutaneous SCC cells and in metastatic SCC cells in combination with chloroquine, an inhibitor of autophagosomal degradation. Hence, Luteolin might be a promising agent for the treatment of cutaneous SCC.